Prognostic value of von Willebrand factor in clinical practice - K. N. Grigoreva; V. O. Bitsadze; J. Kh. Khizroeva; V. I. Tsibizova; M. V. Tretyakova; D. V. Blinov; L. L. Pankratyeva; N. R. Gashimova; F. E. Yakubova; A. S. Antonova; J.-C. Gris; I. Elalamy; et al. (Акушерство, гинекология и репродукция, 2022)
The von Willebrand factor (vWF) is a multimeric plasma glycoprotein, which quantification has important prognostic value. The current literature review demonstrates a relationship between the disease severity and vWF level. For example, von Willebrand disease is characterized by a quantitative/qualitative genetic vWF deficiency resulting in potentially developed massive bleeding, which knowledge can prevent development of formidable complications. We should also not forget about an opportunity of developing acquired Willebrand syndrome most often occurring in response to autoimmune diseases. A marked vWF increase during pregnancy may evidence about developing preeclampsia, whereas in newborns exposed to additional risk factors, it can lead to thrombosis. In cancer patients, a substantially elevated vWF level correlates with low survival, especially in those with ovarian cancer, glioblastomas, esophageal and lung cancer. The emergence of a novel coronavirus infection COVID-19 allowed us to take a fresh look at prognostic value of vWF, because numerous studies show that increased blood plasma vWF:Ag is associated with more adverse outcome in patients with COVID-19. Here, we demonstrate an importance of determining vWF level, because early diagnostics and treatment can improve the outcomes of all such patients.